Perforated Concave Earplug (pCEP): A Proof-of-Concept Earplug to Improve Sound Localization without Compromising Noise Attenuation - Nir Fink; Rachel Levitas; Arik Eisenkraft; Linn Wagnert-Avraham; S. David Gertz; Leah Fostick (Sensors, 2023)
Combat soldiers are currently faced with using a hearing-protection device (HPD) at the cost of adequately detecting critical signals impacting mission success. The current study tested the performance of the Perforated-Concave-Earplug (pCEP), a proof-of-concept passive HPD consisting of a concave bowl-like rigid structure attached to a commercial roll-down earplug, designed to improve sound localization with minimal compromising of noise attenuation. Primarily intended for combat/military training settings, our aim was an evaluation of localization of relevant sound sources (single/multiple gunfire, continuous noise, spoken word) compared to 3M™-Combat-Arms™4.1 earplugs in open-mode and 3M™-E-A-R™-Classic™ earplugs. Ninety normal-hearing participants, aged 20–35 years, were asked to localize stimuli delivered from monitors evenly distributed around them in no-HPD and with-HPD conditions. The results showed (1) localization abilities worsened using HPDs; (2) the spoken word was localized less accurately than other stimuli; (3) mean root mean square errors (RMSEs) were largest for stimuli emanating from rear monitors; and (4) localization abilities corresponded to HPD attenuation levels (largest attenuation and mean RMSE: 3M™-E-A-R™-Classic™; smallest attenuation and mean RMSE: 3M™-Combat-Arms™4.1; pCEP was mid-range on both). These findings suggest that the pCEP may benefit in military settings by providing improved sound localization relative to 3M™ E-A-R™-Classic™ and higher attenuation relative to 3M™-Combat Arms™-4.1, recommending its use in noisy environments.